Visually and Tactually Guided Grasps Lead to Different Neuronal Activity in Non-human Primates - Buchwald, Daniela; Scherberger, Hansjörg (Frontiers in Neuroscience, 2021)
Movements are defining characteristics of all behaviors. Animals walk around, move their eyes toexplore the world or touch structures to learn more about them. So far we only have some basicunderstanding of how the brain generates movements, especially when we want to understandhow different areas of the brain interact with each other.In this study we investigated the influence of sensory object information on grasp planning infour different brain areas involved in vision, touch, movement planning, and movement generationin the parietal, somatosensory, premotor and motor cortex. We trained one monkey to graspobjects that he either saw or touched beforehand while continuously recording neural spikingactivity with chronically implanted floating multi-electrode arrays. The animal was instructed to sitin the dark and either look at a shortly illuminated object or reach out and explore the object withhis hand in the dark before lifting it up.In a first analysis we confirmed that the animal not only memorizes the object in both tasks, butalso applies an object-specific grip type, independent of the sensory modality. In the neuronalpopulation, we found a significant difference in the number of tuned units for sensory modalitiesduring grasp planning that persisted into grasp execution. These differences were sufficientto enable a classifier to decode the object and sensory modality in a single trial exclusivelyfrom neural population activity. These results give valuable insights in how different brain areascontribute to the preparation of grasp movement and how different sensory streams can lead todistinct neural activity while still resulting in the same action execution.